Epitaxy 2018
DOI: 10.5772/intechopen.70259
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy and Device Properties of InGaAs Photodetectors with Relatively High Lattice Mismatch

Abstract: co-workers develop an h-BN/MoTe 2 /graphene/SnS 2 /h-BN van der Waals heterostructure to realize an ultrahigh-sensitivity broadband (405-1550 nm) photodetector, due to its unique advantages for high-efficiency light absorption and exciton dissociation. Graphene plays a key role in enhancing the sensitivity and broadening the spectral range, providing a viable approach toward future ultrahigh sensitivity and broadband photodetectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Certainly, the tunability of the InGaAs detection window via indium enrichment is an interesting property with important technological outcomes; regrettably, indium enrichment also translates to an increase in the lattice mismatch between the InGaAs alloy and the InP substrate, on which the former is typically epitaxially grown or vapor deposited. 34,36 This mismatch causes structural defects that ultimately reduce the optical performances of the material, 36 leading to dark current-induced sensitivity loss, 37 which can be only in part modulated via either thermoelectronic-or cryo-cooling. At present, research towards commercially mature, cost effective, low-noise NIR and SWIR detectors is still in progress.…”
Section: Overview Of Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, the tunability of the InGaAs detection window via indium enrichment is an interesting property with important technological outcomes; regrettably, indium enrichment also translates to an increase in the lattice mismatch between the InGaAs alloy and the InP substrate, on which the former is typically epitaxially grown or vapor deposited. 34,36 This mismatch causes structural defects that ultimately reduce the optical performances of the material, 36 leading to dark current-induced sensitivity loss, 37 which can be only in part modulated via either thermoelectronic-or cryo-cooling. At present, research towards commercially mature, cost effective, low-noise NIR and SWIR detectors is still in progress.…”
Section: Overview Of Challengesmentioning
confidence: 99%
“…Standard InGaAs detectors (lattice-matched In 0.53 Ga 0.47 As on InP) have sensitivity that ranges from 1000 nm to 1700 nm (Fig. 1, dashed orange prole), 34 allowing access to the second biological window. The sensitivity range can be further pushed to higher wavelengths via indium enrichment (extended In x -Ga 1−x As detectors, 0.53 < x < 1), 35,36 enabling detection windows centered from 1637 to 1811 nm, 36 or even higher up in the short wavelength (SW) IR (∼2200-3000 nm) 34,35 (Fig.…”
Section: Overview Of Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad wavelength tuning range, as well as In0.49Ga0.51P/GaAs wider bandgap hetero system, supported the important applications of this quaternary including LD and PD of longer wavelength for fiber communication and shorter wavelength for optical disc, as well as hetero-junction bipolar transistor (HBT). Exploration and practice had been made based on those arsenide and phosphide for a variety of devices in recent decades [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] , resulting in fruitful results. Based on the binaries above in conjunction with related ternaries and quaternaries, a III-V compound containing five elements of Al, Ga, In and As, P could be constructed, but in fact it is the alloy of six binaries, or known as quasihexahydric inherit and develop characteristics of the binaries.…”
Section: Arsenide and Phosphidementioning
confidence: 99%
“…Hence, the control of the buffer layer interface is essential to reduce the dislocations in the step-graded buffer layers. The previous work has demonstrated that to grow a step buffer before the linear grading buffer is benefit to the crystal quality [18]. In our experiment, we have combined the step-graded buffer layer with the linear-graded buffer layer.…”
Section: Introductionmentioning
confidence: 99%